The Cochrane Collaboration - Vickie P. Overman (Journal compilation 2007 Blackwell Munksgaard, 2007)
The Cochrane Collaboration is an independent, international, non-profit organization. Its main focus is to make up-to-date information about healthcare effects available worldwide.